Making the Modern Slum : The Power of Capital in Colonial Bombay - Chhabria, Sheetal (Book collections on Project MUSE., 2019)
"The modern slum, a global phenomenon once considered an unfortunate but natural side effect of economic progress, now exemplifies failed development. How did Bombay (now called Mumbai) become the quintessential example of such failure? By 1880 Bombay was the most dense and second largest town in the British Empire, just behind London. Yet as laborers and migrants became excluded from what counted as the city, Bombay was beset by agricultural crises that caused recurring waves of famine and plague, justifying interventions that further stigmatized the poor. Grounded in an exploration of the changing political economy through the nineteenth and early twentieth century in land, labor, and housing, this book explores the agrarian origins of Bombay city, the mobility of migrants as they brought Bombay into their orbits, the emergence of housing as a commodity that both reflected and produced social life, and the way housing types were encoded as legitimate or illegitimate to make them legible for administration. It foregrounds the perspective of the laboring and urban poor and challenges assumptions about colonial cities and cities of the global south"--